Comparison of host immune responses to homologous and heterologous type II porcine reproductive and respiratory syndrome virus (PRRSV) challenge in vaccinated and unvaccinated pigs - Li, X.; Beckley, Amy J.; Pappan, L.; Trible, B.; Kerrigan, Maureen A.; Beck, A.; Hesse, Richard A.; Blecha, Frank; Nietfeld, Jerome C.; Rowland, Raymond R.R.; Shi, Jishu N. (My University, 2014)
Porcine reproductive and respiratory syndrome (PRRS) is a high-consequence animal disease with current vaccines providing limited protection from infection due to the high degree of genetic variation of field PRRS virus. Therefore, understanding host immune responses elicited by different PRRSV strains will facilitate the development of more effective vaccines. Using IngelVac modified live PRRSV vaccine (MLV), its parental strain VR-2332, and the heterologous KS-06-72109 strain (a Kansas isolate of PRRSV), we compared immune responses induced by vaccination and/or PRRSV infection. Our results showed that MLV can provide complete protection from homologous virus (VR-2332) and partial protection from heterologous (KS-06) challenge. The protection was associated with the levels of PRRSV neutralizing antibodies at the time of challenge, with vaccinated pigs having higher titers to VR-2332 compared to KS-06 strain. Challenge strain did not alter the cytokine expression profiles in the serum of vaccinated pigs or subpopulations of T cells. However, higher frequencies of IFN-γ-secreting PBMCs were generated from pigs challenged with heterologous PRRSV in a recall response when PBMCs were re-stimulated with PRRSV. Thus, this study indicates that serum neutralizing antibody titers are associated with PRRSV vaccination-induced protection against homologous and heterologous challenge.
Keywords: PRRS virus; Porcine reproductive and respiratory syndrome; Pigs